1983
DOI: 10.2337/diacare.6.4.361
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Circulating Glucose and Triglyceride Concentrations and Their Interactions with Other “Risk Factors” as Determinants of Arterial Disease in Nine Diabetic Population Samples from the WHO Multinational Study

Abstract: In 9 of the 14 national samples of diabetic patients assembled for the WHO Multinational Study of Vascular Disease in Diabetes additional laboratory data made it possible to relate manifestations of macrovascular disease to blood glucose concentrations as well as to diabetes duration and to other potential determinants. In five of the samples, serum triglyceride concentrations were also measured and were included in simple and multivariate analyses. Ischemic heart disease defined from Minnesota-coded EKGs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
131
4
7

Year Published

1985
1985
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 424 publications
(153 citation statements)
references
References 2 publications
6
131
4
7
Order By: Relevance
“…In a subset of 9 of the original 14 centres, 8 of them included in the follow-up, fasting venous blood was collected at the baseline examination and glucose estimated by the local`true glucose' method. The methods used have been described elsewhere [11]. The geometric mean fasting glucose values are shown by centre in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…In a subset of 9 of the original 14 centres, 8 of them included in the follow-up, fasting venous blood was collected at the baseline examination and glucose estimated by the local`true glucose' method. The methods used have been described elsewhere [11]. The geometric mean fasting glucose values are shown by centre in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…There is considerable evidence indicating that plasma triglyceride concentrations are higher than normal in patients with NIDDM [32], and that this change is associated with increased risk of CHD in these patients [33,34]. However, the link between a high plasma triglyceride concentration and CHD is far from obvious.…”
Section: Discussionmentioning
confidence: 96%
“…65 In this cross-sectional study, triglyceride levels were significantly higher among subjects with major Q-wave abnormalities compared with subjects without such abnormalities. Multivariate analysis using logistic regression revealed that the triglyceride association remained significant, independently of age, adiposity, cholesterol, and systolic blood pressure.…”
Section: Studies In Diabeticsmentioning
confidence: 90%